Numerous relative clauses permutation invariance, anti-restrictiveness, triviality - Pinton, Lorenzo (Proceedings of the Amsterdam Colloquium, 2022)
In this paper we study the different patterns that gather-like and numerous-like predicates present in restrictive relative clauses. We argue that numerous is generally bad in restrictive relative clauses, because when it applies to a predicate that denotes a complete join semilattice, triviality arises with the definite plural. As a consequence, we predict that restrictive numerous is fine if it applies to predicates that do not give rise to complete join semilattices. This is indeed the case for complex predicates like gathered students, whenever the collective predicate gather is not pluralized.